Pelatihan Penyusunan Laporan Keuangan Sederhana Bagi untuk Meningkatkan Transparansi Usaha di Desa Karya Jadi Kec. Batang Serangan Kab. Langkat Prov. Sumatera Utara: Pengabdian - Berlin Barus; Dumariani Silalahi; Monang Tarigan; Harlen Silalahi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the skills of micro-entrepreneurs in Karya Jadi Village, Batang Serangan District, Langkat Regency, North Sumatra Province, in preparing simple financial reports as an effort to strengthen business transparency. The implementation method uses an interactive lecture approach and Focus Group Discussion (FGD), which allows participants to understand basic accounting theory while practicing it directly. A total of 25 participants participated in this activity consisting of culinary, trade, and small service entrepreneurs. The results of the pre-test and post-test showed an average increase in understanding of 69.4%, especially in the ability to record transactions and prepare simple profit and loss and cash flow statements. The program also involved collaboration between academics, village governments, and local communities, creating synergy that strengthened the program's effectiveness and sustainability. Results demonstrated that the combination of lectures and focus group discussions (FGDs) was effective in improving financial literacy, building a culture of transparency, and strengthening accountable business governance at the village level. This program is expected to be replicated in other areas with similar characteristics to support sustainable rural economic development.